REDESAIN RUANG TERBUKA PUBLIK DI TOLITOLI (STUDI KASUS TAMAN KOTA GAUKAN MUHAMMAD BANTILAN) - Agustina, Yuniar; Yusuf, Ramdan; Purnomo, Dwi (ANALOGI : Arsitektur, Lingkungan Binaan & Planologi, 2024)
Gaukan Muhammad Bantilan City Park is located in the city center and functions as a place for social activities such as sports, recreation, socialization, and street vendor activities (PKL), in addition to its ecological function. Gaukan Muhammad Bantilan City Park is adjusted to the community's needs, which can attract the interest of the people of Tolitoli Regency to reintroduce history without explaining the history and attracting local and foreign tourists to visit Tolitoli Regency. The purpose of the redesign is to meet the functional aspects of the needs of each user's space. The qualitative research method uses a descriptive approach, assisted by primary and secondary data. Data analysis includes data display, data grouping, and data reduction. The results of the study stated that the Gaukan Muhammad Bantilan City Park, through elements of public space design, supporting facilities in the park, successful public open spaces, comfort and impression (comfort and image), security, cleanliness, vegetation, seating, lighting, access in and out, function and activity (use and activity), activity, usefulness, social ability (sociability), can provide comfort to users of public open spaces. Architecture must consider how space can be a place for active social interaction, functioning as a comfortable recreational space. Considering social, cultural, and economic factors, the design of public open spaces can strengthen local identity and create an environment that supports the welfare of the community as a whole.